Acute cardiovascular and metabolic responses to a single line dance session - Rusdiawan Rusdiawanan; Mochamad Purnomo; Sumaryanti Sumaryanti; José Vicente García Jiménez; Adi Pranoto (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2026)
Physical inactivity among middle-aged women remains a major contributor to increased cardiovascular and metabolic health risks worldwide. This study sought to examine the acute cardiovascular and metabolic responses during a 45-minute instructor-led line dance session in physically active middle-aged women. A single-session cross-sectional observational design was employed involving thirty participants aged 30–50 years who completed a standardized routine consisting of warm-up, main session, and cool-down phases. Every participant wore a Polar H10 heart-rate monitor and an accelerometer to collect data throughout the session. Exercise intensity was classified into five heart-rate zones according to the percentage of maximum heart rate (HRmax), while caloric expenditure was estimated using heart-rate data and MET values. Descriptive analysis was employed to delineate cardiovascular and metabolic responses, while multivariate regression assessed predictors of total caloric expenditure, controlling for age and body mass index (BMI). The average intensity of the participants' exercise was 72.8 ± 5.6% HRmax (132.5 ± 10.4 bpm), the mean energy cost was 245.6 ± 35.2 kcal, and the MET value was 4.2 ± 0.6. The majority of the session duration was allocated to Zone 3 (38.2 ± 6.1%) and Zone 4 (18.4 ± 4.7%). The time spent in Zones 3–5 was a significant predictor of caloric expenditure (β = 0.68, p < 0.001, R² = 0.74). These findings demonstrate that a single 45-minute instructor-led line dance session produces moderate-to-vigorous acute cardiovascular strain and metabolic responses, as reflected by heart rate zone distribution and energy expenditure in physically active middle-aged women.